Fitrah Guidance And Counseling In The Elimination Of Delinquency - Syara Jayanti; Imas Kania Rahman; Akhmad Alim (Program Studi Bimbingan Konseling dan Pendidikan Islam, 2020)
At present, the delinquency rate of students continues to increase. This indicates that it is needed for an approach other than the learning process, and the effort is guidance and counseling. But in reality, religious counseling when viewed from operational technical aspects, the intervention model used is not as effective as the intervention model that has been developed in western counseling in general. Focus problem in this study trying to find a creative Islamic guidance and counseling approach, in the effort to eliminate delinquency. The approach used in this research is thematic tafseer and Focus Group Discussion (FGD). The researcher focuses on one topic related to a particular problem then the researcher collects Al-Qur'an verses that are related both legally and legally and looks at the interpretation of the verse and copies and analyzes the results of the FGD to be presented as research results. The analytical method used is a qualitative method for finding and designing approach. The results of the thematic tafseer and FGD studies show that the fitrah guidance and counseling in the Qur'an has been successfully formulated in the form of material content used in the fitrah Guidance and Counseling procedures such as simulations of water and black ink, hawa nafsu vs hidayah techniques, tadabbur hadith a sin is one black point, tadabur hadith parable of Saleh friends accompanied by simulations and prayer therapy, zikrullah therapy, muraqabatullah, Social therapy (family therapy, community therapy, friendship with ulama). All material content is designed in a Guidance and Counseling approach in eliminating delinquency summarized in seven stages of the procedure, namely Muqaddimah, Recognize (i'tirof), Regret (nadam), Follow the Fitrah of God, Determine not to repeat ('adamut tikror), Husnudzon Billah and Self Improvement (Ishlah adz-Dzat).